2013
DOI: 10.1111/ijac.12116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ZnO–B2O3 Addition on the Microstructure and Microwave Properties of Low‐Temperature Sintered Barium Strontium Titanate (BST) Thick Films

Abstract: composite thick films have been investigated regarding their suitability as low-temperature sintered tunable microwave dielectrics. The investigations showed that already a small amount of ZnO-B 2 O 3 additive can remarkably reduce the sintering temperature down to 900°C. Microstructural investigations of the thick films revealed the formation of an amorphous intergranular phase and a clustering of particles for high additive amounts. The microwave characterization showed a reduction in relative permittivity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…24,26 Previous investigations showed that a lower porosity can be achieved by using a mixture of coarse and fine grained powders 27 or a higher amount of sintering additive. 19 The dielectric loss of the material increases with frequency. This behavior is known for tunable dielectric ceramics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…24,26 Previous investigations showed that a lower porosity can be achieved by using a mixture of coarse and fine grained powders 27 or a higher amount of sintering additive. 19 The dielectric loss of the material increases with frequency. This behavior is known for tunable dielectric ceramics.…”
Section: Resultsmentioning
confidence: 99%
“…The powder was mixed with 0.76% w/w ZnO (Nanostructured & Amorphous Materials, Houston, TX) and 0.65% w/w B 2 O 3 (Alfa Aesar, Ward Hill, MA) to obtain a composition suitable for a low-temperature co-firing process. The material composition is based on recent investigations of Kohler et al, 19 who showed that even a small amount of additives is suitable to reduce the sintering temperature of screen-printed BST thick films to temperatures of 900°C and below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements at further frequencies are ongoing to fully verify the simulations. To further improve the performance of this technology, metal dielectric-metal parallel plate varactors [8] are developed to reduce the complexity and required bias voltage of the TMNs (below 200 V). Investigations of the technology and varactors beyond 20 W of input power are ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…However, the achieved microwave characteristics, such as a Figure of merit (FoM) of 6.5°/dB for an integrated phase shifter, are of limited suitability for the use in phased array applications. In recent studies, BST‐ZnO‐B 2 O 3 composite thick‐films have been investigated regarding their suitability as low‐temperature sintered tunable microwave dielectrics . Based on this material, fully screen‐printed MIM capacitors and phase shifters could be fabricated on alumina substrates which showed a considerable improvement compared to other studies .…”
Section: Introductionmentioning
confidence: 99%